Fate of Listeria monocytogenes in tissues of experimentally infected cattle and in hard salami. - Johnson, J L (1988)
Muscle, organ, and lymphoid tissues of four Holstein cows experimentally inoculated (intravenously) with Listeria monocytogenes were examined 2, 6, or 54 days postinoculation for the presence of the organism by direct plating and cold enrichment procedures. L. monocytogenes was isolated from 66% of the tissues sampled; 38% of the isolations were attributed to the use of cold enrichment. Isolation of the organism from muscle tissue was possible only with animals inoculated 2 days before slaughter. The fate of L. monocytogenes during the manufacture and storage of fermented hard salami made from this meat also was determined. Three sausage treatments were evaluated: (i) uninoculated control sausage, (ii) "naturally" contaminated sausage (NC) made from meat of an experimentally inoculated cow, and (iii) sausage made from beef inoculated with a laboratory culture of L. monocytogenes (I). Initial Listeria levels in NC and I sausage were 10(3) CFU/g in trial 1 and 10(4) CFU/g in trial 2. Numbers of L. monocytogenes decreased by approximately 1 log10 CFU/g during fermentation and decreased further during drying and refrigerated storage. Small numbers (less than or equal to 20 CFU/g) of L. monocytogenes were present in I and NC sausage at the end of 12 weeks of refrigerated storage; recovery of these organisms generally depended on the use of an enrichment procedure. The results indicate that L. monocytogenes does not multiply during the fermentation and drying processes typical of hard salami manufacture but that survival may occur if the organism is initially present at greater than or equal to 10(3) CFU/g.